Event management planning, organising, leading and controlling - Henry, Michael; Garner, Simon; Video Education Australasia (Australia : Video Education Australasia, 2005)
This program explores what is needed to plan an event and evaluate its successfulness by providing a behind-the-scenes look at the staging of the Eureka 150 event held in Ballarat, Victoria in 2005
Title from title screen
DVD format
Keywords: Special events -- Planning; Business meetings -- Planning